Relationship between Lower Limb Angular Kinematic Variables and the Effectiveness of Sprinting during the Acceleration Phase - Artur Struzik; Grzegorz Konieczny; Mateusz Stawarz; Kamila Grzesik; Sławomir Winiarski; Andrzej Rokita (Applied Bionics and Biomechanics)
The ability to reach a high running velocity over a short distance is essential to a high playing performance in team games. The aim of this study was to determine the relationship between running time over a 10-meter section of a 30-meter sprint along a straight line and changes in the angle and angular velocity that were observed in the ankle, knee, and hip joints. The possible presence may help to optimize motion efficiency during acceleration sprint phase. Eighteen girls involved in team sports were examined in the study. The Fusion Smart Speed System was employed for running time measurements. The kinematic data were recorded using the Noraxon MyoMotion system. Statistically significant relationships were found between running time over a 10-meter section and the kinematic variables of hip and ankle joints. An excessively large flexion in hip joints might have an unfavorable effect on running time during the acceleration phase. Furthermore, in order to minimize running time during the acceleration phase, stride should be maintained along a line (a straight line) rather than from side to side. It is also necessary to ensure an adequate range of motion in the hip and ankle joints with respect to the sagittal axis.